2014
DOI: 10.3747/co.21.1663
|View full text |Cite
|
Sign up to set email alerts
|

Piloting a Regional Collaborative in Cancer Surgery Using a “Community of Practice” Model

Abstract: pathways in breast, colorectal, and prostate cancer disease sites; rectal cancer surgery centralization; increased use of sentinel lymph node biopsies in breast cancer surgery; and decreased positive surgical margin rates in prostate cancer. ConclusionsImproved quality is likely a result of diverse confounding factors. The deliberately cultivated multihospital multidisciplinary cops have contributed to positive structural and functional change in cancer surgery in the region. This regional cop model has the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…CoP is a social phenomenon, hence physical interaction between CoP members is regarded as important for its success (Fung‐Kee‐Fung, Boushey, Watters, et al, ; Iaquinto et al, ; Orr, ; Wenger et al, ), whereas reduced face‐to‐face interaction is found to have negative effects on CoP performance (Schenkel & Teigland, ). A meeting between CoP participants must provide a risk‐free zone, which caters for participants' ability to ask questions without risk of sanction (Borzillo, ), enable in‐depth and undisturbed discussions (Orr, ), and facilitate a collaborative work effort (Fung‐Kee‐Fung, Boushey, & Morash, ).…”
Section: Communities Of Practicementioning
confidence: 99%
“…CoP is a social phenomenon, hence physical interaction between CoP members is regarded as important for its success (Fung‐Kee‐Fung, Boushey, Watters, et al, ; Iaquinto et al, ; Orr, ; Wenger et al, ), whereas reduced face‐to‐face interaction is found to have negative effects on CoP performance (Schenkel & Teigland, ). A meeting between CoP participants must provide a risk‐free zone, which caters for participants' ability to ask questions without risk of sanction (Borzillo, ), enable in‐depth and undisturbed discussions (Orr, ), and facilitate a collaborative work effort (Fung‐Kee‐Fung, Boushey, & Morash, ).…”
Section: Communities Of Practicementioning
confidence: 99%
“…Pioneered by Lave and Wenger (1991), CoPs have been defined as “group[s] of people who share a concern or a passion for something they do, and who learn how to do it better as they interact regularly” (Wenger-Trayner and Wenger-Trayner 2015, 1). Most publications on CoP are in the fields of medicine (Barnett et al 2013; Fung-Kee-Fung et. al.…”
Section: Introductionmentioning
confidence: 99%
“…Participants in the @AskAnatomist tweet chat were from a variety of professional disciplinary backgrounds, including anatomists, histologists, embryologists, and evolutionary biologists, as well as some student participants from both within and external to healthcare professional education. This multidisciplinary engagement is not only demonstrated in other communities of practice, but this collaborative approach has also been found to be valuable, particularly in clinical settings where this can improve cooperation (Fung‐Kee‐Fung et al, ; Roberts, ).…”
Section: Discussionmentioning
confidence: 99%